Phenolic profile, in vitro antimicrobial and in vivo diuretic effects of endemic wild thyme Thymus comosus Heuff ex. Griseb. (Lamiaceae) from Romania - Babotă, Mihai; Frumuzachi, Oleg; Nicolescu, Alexandru; Stojković, Dejan; Soković, Marina; Rocchetti, Gabriele; Zhang, Leilei; Lucini, Luigi; Crișan, Gianina; Mocan, Andrei; Voștinaru, Oliviu (Frontiers in Pharmacology, 2023)
Thymus comosus Heuff ex. Griseb. (Lamiaceae) is a wild thyme species endemic for Romanian Carpathian areas, frequently collected as substitute for collective herbal product Serpylli herba, cited as antibacterial and diuretic remedy in traditional medicine. The present study aimed to evaluate the in vivo diuretic effect and in vitro antimicrobial properties of three herbal preparations (infusion—TCI, tincture—TCT and an hydroethanolic extract prepared through an optimized ultrasound-assisted method—OpTC) obtained from the aerial parts of T. comosus Heuff ex. Griseb, also evaluating their comprehensive phenolic profile. In vivo diuretic effect was tested using Wistar rats treated orally with each herbal preparation (125 and 250 mg/kg dispersed in 25 ml/kg isotonic saline solution) and quantified based on cumulative urine output (ml), diuretic action and diuretic activity. Additionally, sodium and potassium excretion were monitored using a potentiometric method with selective electrodes. In vitro antibacterial and antifungal activities were assessed using p-iodonitrotetrazolium chloride assay against six bacterial strains and six fungal strains by monitoring minimum inhibitory concentration (MICs), minimum bactericidal concentrations (MBCs) and minimum fungicidal concentrations (MFCs). Finally, phenolic profile of the aforementioned herbal extracts was evaluated using an ultra-high-pressure liquid chromatography (UHPLC) coupled with high-resolution mass spectrometry (HRMS) method to check the impact of the different preparations on the most abundant and significant compounds. All the extracts exerted a mild diuretic action, TCT and OpTC inducing the most intense diuretic effect. Both herbal preparations produced a statistically significant, dose-dependent and gradual increase of the urine output, the effect being more intense at 24 h (6.63–7.13 ml/24 h). Potentiometric evaluation of urine samples collected from treated rats revealed a clear and mild natriuretic and kaliuretic effect after the administration. In terms of antimicrobial activity, E. coli (MIC—0.38 mg/ml), B. cereus (MIC—0.75 mg/ml)), Penicillium funiculosum and P. verrucosum var. cyclopium (MIC—0.19 mg/ml) showed the greater sensitivity to the tested extracts, respectively. UHPLC-HRMS screening showed that the bioactive potential of T. comosus herbal preparations was likely related to the higher amounts of phenolic acids (including rosmarinic acid), flavonoids (mainly flavones and derivatives) and other phenolics (such as different isomers of salvianolic acids) in their composition. The obtained results support the ethnopharmacological evidence regarding the mild diuretic and antibacterial potentials of the endemic wild thyme T. comosus, this study being the first one that assessed the aforementioned bioactivities for this species.